Diagnosis and management of intestinal partial obstruction in a loggerhead turtle (Caretta Caretta) - Williams, S.; Dennison, S.; Dunnigan, B.; Moore, B.; Nicholson, J.; Zagzebski, K.; Ketten, Darlene; Cramer, S.; Arruda, J. (American Association of Zoo Veterinarians, 2013)
A loggerhead sea turtle (Caretta caretta) was suspected of ingesting rubber suction cups during rehabilitation following a cold-stun event. Survey radiographs were inconclusive. Computed tomography (CT) was performed to determine whether the objects had been ingested after traditional radiographs failed to resolve the material. The items were identified, and a partial obstruction was diagnosed. The case was managed with medical therapy using white petrolatum and light mineral oil administered to the turtle in fish for 3 wk. The CT exam was repeated 2 wk into the therapy. A persistent partial obstruction was identified; however, progression of the foreign objects through the intestinal tract was evident and continued medical mangement was deemed appropriate. The foreign bodies were passed with feces 26 days after ingestion. © 2013 American Association of Zoo Veterinarians.